A BLOCKCHAIN-BASED APPROACH TO PREVENT HIDDEN CONTAGION OF COVID-19 - Samen Anjum Arani; Md. Rashed Ibn Nawab; Md. Tanvir Rahman; Moniruz Zaman (Compiler, 2020)
The unprecedented outbreak of COVID-19 has become a grave concern worldwide because of its highly infectious nature. Besides extensive research on developing vaccine or medicine to prevent this virus attack, many technology-based solutions are also getting more importance as no one knows till date how to put a full stop on it. Being first conceptualized in 2008, blockchain technology gained enormous popularity in the cryptocurrency domain. However, nowadays, blockchain has also become popular in the healthcare domain as a privacy-preserving and data authenticity technique. The primary goal of our experiment is to develop a framework which can utilize the features of permissioned blockchain and maintain the fully controlled sharing of confidential health record to exhibit the health status and COVID-19 history of a patient using a mobile QR code based solution. So, the administrative team of any public place can be aware of the health condition of any people who are using this platform to prevent the unaware and hidden contagion of COVID-19. This article is the first of its kind to propose such a method to aid in solving this crisis. In our experiment, we have shown that Hyperledger Fabric as a base technology along with a robust user registration algorithm and data accessibility can solve the problem under consideration with a minimal health record of the patient. The proposed architecture also offers the patient more control over the health record, where the healthcare service provider assures the authenticity of the data, and the intrinsic feature of the blockchain technology makes it immutable.